The creation of story and character through formal opposition and disunity. Issue 2 (1st April 2018) - Spence, Peter
A series of striking visual tropes contrast with a matter of fact voice-over to create the bold formal strategy of the film-poem Flimmer. Sound and image compete for primacy in an interplay of dialogue and visuals.